2006
DOI: 10.1108/09556220610668482
|View full text |Cite
|
Sign up to set email alerts
|

Tearing and tensile strength behaviour of military khaki fabrics from grey to finished process

Abstract: Purpose -This paper seeks to report an experimental investigation on the tearing and tensile strength behaviour of military khaki fabrics from grey to finished process. Design/methodology/approach -Uses three different types of military fabric (3 up 1 down twill), differing in type of constituent yarns (ring/rotor) in order to test their tearing and testing strength behaviour. Findings -Tearing strength of fabric is found to be very much susceptible to change due to the process variation, while fabric tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Although there are simple ways to measure such strength, theoretical prediction and modeling remain diffi cult, due to the many variables that contribute to the complicated mechanisms involved in the tearing process (Hamkins and Backer, 1980;Krook and Fox, 1945;Mukhopadhyay et al, 2006;Scelzo et al, 1994aScelzo et al, , 1994bTaylor, 1959;Teixeira et al, 1955;Teutelink et al, 2003;Frydrych, 2004, 2005;Zhong et al, 2004). Examples include the development of a del-zone in a tongue tear test (see Fig.…”
Section: Fabric Tearmentioning
confidence: 97%
“…Although there are simple ways to measure such strength, theoretical prediction and modeling remain diffi cult, due to the many variables that contribute to the complicated mechanisms involved in the tearing process (Hamkins and Backer, 1980;Krook and Fox, 1945;Mukhopadhyay et al, 2006;Scelzo et al, 1994aScelzo et al, , 1994bTaylor, 1959;Teixeira et al, 1955;Teutelink et al, 2003;Frydrych, 2004, 2005;Zhong et al, 2004). Examples include the development of a del-zone in a tongue tear test (see Fig.…”
Section: Fabric Tearmentioning
confidence: 97%
“…This research achievement will contribute to the prediction of damage growth and the ability to compare different fabric materials for their damage tolerance. Mukhopadhyay et al (2006) reported an experimental investigation on the tearing and tensile strength of military khaki fabrics from grey to finished process (such as bleaching and dyeing). The results showed that tensile strength is relatively less sensitive while tearing strength dropped significantly during the grey to finished process.…”
Section: Introductionmentioning
confidence: 99%
“…The finishing treatment as easy care or coating reduce the tearing strength due to restrict in freedom of movement of the yarns under loading [37]. So, it clear that tearing strength is more dependent of the of the fabric construction [41] …”
Section: Tear Strength (Warp and Weft Direction)mentioning
confidence: 99%
“…This failure causes the load being transferred to the adjacent yarn and thus fails in turn. Thought greater extensibility or reduced frictional constraints allow the yarns to bunch at the tear, and therefore increase the tearing strength [40], it is clear that higher yarn strength may not necessarily lead to higher tear strength [41].…”
Section: Tear Strength (Warp and Weft Direction)mentioning
confidence: 99%